Estudio de la disposición final de Desechos Sólidos en el Relleno Sanitario de la Mancomunidad Pujilí-Saquisilí. - Mayo Cualchi, Jenifer Azucena (2017)
The present study of the final disposition of solid wastes in the sanitary landfill of the Pujilí - Saquisilí Commonwealth; Was carried out in the emergent cell, located to the south-east of the Pujilí canton, in the province of Cotopaxi, 8.5km from the canton Latacunga and 6.5km from the Pujilí canton; Belonging to the sector of Inchapo. For the study were set as objectives: The diagnosis of solid waste management during the final disposal of the same, the characterization of the common solid waste of the Pujilí canton that enters the sanitary landfill and the proposal of a plan for the management of the final disposition of the solid wastes. Generating qualitative and quantitative information on the characteristics of the solid waste generated in the Pujilí Canton belonging to the Commonwealth. For which, in order to comply with the first objective, the diagnosis was made using records of the waste entrance as evidence. With the help of a matrix that allowed collecting data from the number of times the collectors enter the sectors, and in turn verify the use of Personal Protective Equipment (EPI's) inside the emerging cell. Subsequently, and to meet the second objective, we continue the weighing of one of the Commonwealth collectors; the Same that was weighed it in state full and empty , to estimate the amount of residues that occur in the canton of Pujilí and are arranged daily in the sanitary landfill of the Commonwealth; Then, with the help of the cuarteo method, a characterization of each of the recollectors covering the three collection routes was carried out in the Pujilí canton, where the percentage and type of solid wastes that arrived at the landfill were determined; Using photos and analysis of results that will serve as evidence. When estimating the common solid waste produced daily throughout the canton and with the help of data obtained by the INEC in 2010 of the population and with tese was could the per-capita porcent could be determined in kg / day /hab. Finally, and after these previous